2013
DOI: 10.5146/tjpath.2017.01406
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous cervical minimal deviation adenocarcinoma, gastric type adenocarcinoma and lobular endocervical glandular hyperplasia along with stil in peutz-jeghers syndrome: eliciting oncogenesis pathways

Abstract: ABSTRACTwe describe an unusual case of a Peutz-Jeghers syndrome associated with a composite synchronous cervical neoplasia comprising precursor "lobular endocervical glandular hyperplasia (LEGH)", "minimal deviation adenocarcinoma (MDa)" and "gastric-type adenocarcinoma (GTa)" along with a serous tubal intraepithelial lesion (STIL) in the right fallopian tube. a 24-year-old woman presented with a white mucoid discharge and bleeding per vaginum for one year. Histopathological evaluation showed MDa & GTa in FIGo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…High-risk human papillomavirus (HR-HPV) is currently indicated to be associated in the carcinogenesis of ADC of UC 16 . There is lack of targeted therapy in CC due to poor understanding of signaling pathways underlying CC development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…High-risk human papillomavirus (HR-HPV) is currently indicated to be associated in the carcinogenesis of ADC of UC 16 . There is lack of targeted therapy in CC due to poor understanding of signaling pathways underlying CC development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive literature search produced 1564 publications; 46 studies were identified that focused on lobular endocervical glandular hyperplasia/gastric-type adenocarcinoma in patients with Peutz-Jeghers syndrome. Thirty-eight (83%) were case reports/case series that met the inclusion criteria and were included in the analysis 13 14 16 19–53. The remaining eight studies were original research (five) or reviews (three) and were excluded from the analysis.…”
Section: Resultsmentioning
confidence: 99%
“… 8 Neyaz et al described the case of a Peutz–Jeghers syndrome associated with a composite synchronous cervical neoplasia comprising precursor LEGH, MDA and gastric-type adenocarcinoma (GTA) along with a serous tubal intraepithelial lesion (STIL) in the right fallopian tube. 9 …”
Section: Discussionmentioning
confidence: 99%
“…8 Neyaz et al described the case of a Peutz-Jeghers syndrome associated with a composite synchronous cervical neoplasia comprising precursor LEGH, MDA and gastric-type adenocarcinoma (GTA) along with a serous tubal intraepithelial lesion (STIL) in the right fallopian tube. 9 Peng et al reported the case of 33-year-old female patient with Peutz-Jeghers syndrome (PJS) with both cervical micro-deviation adenocarcinoma (MDA) and gastrictype adenocarcinoma (GTA). According to the analysis of immunohistochemical indexes such as MUC6, CK7, p16, ER, PgR, CEA, HIK1083 and CK20 in the two pathological areas, it proved the continuity between gastric adenocarcinoma and MDA, supporting the hypothesis that GTA originated from MDA de-differentiation.…”
Section: Dovepressmentioning
confidence: 99%